Analisis Ground Vibration Pada Kegiatan Peledakan Batuan Penutup Yang Aman Terhadap Bangunan Pada PT. Rinjani Kartanegara Site Bakungan Kecamatan Loa Janan Provinsi Kalimantan Timur (Jurnal Geologi Pertambangan (JGP), 2018)
ABSTRACTThe purpose of this study was to determine the amount of ground vibration that can be accepted by the building with a certain distance. While the goal is to measure the value of the vibration of the ground (ground vibration) the result of blasting activities with the parameters of peak particle velocity (PPV), which consists of a transverse, vertical and longitudinal, predicting the value of the peak particle velocity on blasting activities the next, and Determine the distance and stuffing maximum material explosives per delay by the safe limit ground vibrations. The research activities carried out is by collecting measurement data, stuffing explosives per delay, the distance between measurement locations to the blasting location and other technical data that will be used to predict ground shaking in the next detonation.The research results using peak particle velocity equation with the equation of the United State Bureau Of Mines. At the blasting activities during the month of December 2016 until February 2017 average values obtained constants / site factor of K = 2813.767 and m = -1.6 with vibration generated remained at safe levels based on ISO 7571 in 2010. Constant value is used as a reference in the calculation of ground vibration during December 2016 - February 2017 actual equation PPV = (0.6 to 1.44) PPV predictions. From the analysis of the scaled distance of ground vibration obtained SD = 38 for the predicted amount of explosives per delay stuffing with a variety of different distances. Based on a scaled prediction calculation specified distance of ground vibration, the value to be obtained in subsequent blasting proven safe to the criteria of class building 5 SNI 7571 amounted to 3.53 mm / s ≤ actual PPV ≤ 12 mm / s. Keyword : Ground Vibration, Blasting, Scale Distance, United State Bureau Of                    Mines, Peak Particle Velocity
Keywords: Ground Vibration; Blasting; Scale Distance; United State Bureau Of